Parameter Estimation in Modeling of Photovoltaic Panels Based on Datasheet Values - Can, Hayrettin; Ickilli, Damla (Asme, 2014)
The increasing demand for renewable energy sources in recent years has triggered technological advancements in photovoltaic (PV) panels. Widespread use of large-scale PV units has revealed the sensitivity in PV panel modeling needed to estimate the amount of energy produced in different environmental conditions. For the formation of a PV panel model, parameters should be obtained by numerically solving characteristic equations of a transcendental nature. This study preferred using the Newton Raphson (NR) method owing to the suitability of equation structure. It is crucial that numerical solution starts with proper initial values. This study proposes a new approach to identifying initial values in order to decrease calculation time and increase the speed of numerical convergence. The proposed method was used in parameter estimation for different panel models. And, it was observed that owing to this method, the system converged with less iteration and the problem of failing to solve the system because of inappropriate initial values were eliminated. Convergence was obtained and the solution needed less iteration in all models.
Keywords: PV panel; parameter estimation; modeling